Factors Influencing E-Wallet Payment Usage in E-Marketplace: Digital Marketing Class Student Survey - Pretisila Kartika Putri; Rezky Pramurindra (Kompartemen : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine what factors influence the preferences of marketplace consumers in making payments. Several payment methods were identified in this study on several e-marketplaces in Indonesia. The factors studied in this study are perceived ease of use, perceived usefulness and experience. The data was obtained based on the distribution of questionnaires to digital marketing class students at Siliwangi University Indonesia, totaling 33 respondents. Multiple regression analysis using SPSS was chosen by researchers in conducting this study. The results show that perceived ease of use, perceived usefulness, and experience has a positive effect on e-marketplace payment preferences.